The Aristotelian Conception of Principle as the Theoretical Foundation for a Healthy Cultural Relativism - Ibarra , Silviano de Jesús Anda (International Journal of Membrane Science and Technology, 2023)
to elucidate if the three most accepted modalities of cultural relativism -descriptive, normative, and cognitive- are philosophically valid, and consequently healthy for knowledge development, cultural understandings, and knowledge reliability. Theoretical Framework: the theoretical ideas oscillated among the pure reasoning behind cultural relativism, culture theory, the premises of Husserl’s phenomenology, and the Aristotelian notions of principle and relation, among others. Design / Methodology / Approach: the Aristotelian dialectic, which poses an idea to discussion, analyzes it to discard any contradiction; if contradiction emerges, the data and notions behind the discussed idea are hierarchized to the main principles of knowledge for improvement or correction. Findings: the only valid and healthy modality of cultural relativism is the “descriptive” one because it truly seeks the approach and understanding of alterity/otherness as the cultural relativism reasoning claims. Research, Practical & Social implication: the configuration of normative and epistemological systems based on cultural relativism is contradictory, unhealthy, and dangerous for culture and research conclusions. Originality / Value: this work consists of the attempt to conciliate the foundations of western philosophy with the contemporary philosophical doctrines as an invitation to achieve the ideal of culture: set a proper world for humanity.